(untitled) (Geologica Macedonica, 2013)
Within the frame of the trepel deposits (Fig. 1) near Suvodol village, Bitola city it was discovered(Lj. Petreski) an earthy-cryptocrystalline vivianite occurrence. The examined vivianite sample was confirmed byX-ray powder diffraction, chemical, SEM, DTA/TG, infra-red analyses. The treated vivianite sample actually representsa typical earthy-cryptocrystalline variety (Fig. 2) with a peculiar progressive oxidation state of Fe2+ to Fe3+(FeO/Fe2O3 contents nearly 1:1). X-ray powder diffraction, DTA/TG-data are in quite good concordance with literaturedata.